The Swiss model of federalism. Some lessons for the European Union - Nitszke, Agnieszka (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2014)
The federal principle in Switzerland has been developing for centuries. It was a process that has not always proceeded in a peaceful manner. The creation of Swiss statehood required reconciling different groups and interests. Today’s federal solutions in Switzerland allow for the peaceful co-existence of different language and religious groups. Another challenge is to reconcile the interests of wealthy and poor cantons. Understanding how this happened can provide guidance for further integration within the European Union, which in many aspects might be compared to Switzerland.

Zasada federalizmu w Szwajcarii rozwijała się przez wieki. Był to proces, który nie zawsze przebiegał w sposób pokojowy. Stworzenie szwajcarskiej państwowości wymagało pogodzenia różnych grup i interesów. Dzisiejsze rozwiązania federalne w Szwajcarii umożliwiają pokojowe współistnienie różnych grup językowych i religijnych. Kolejnym wyzwaniem było pogodzenie interesów bogatych i biednych kantonów. Poznanie mechanizmów federalizmu szwajcarskiego może stanowić wskazówkę dla dalszej integracji w ramach Unii Europejskiej, która pod wieloma względami przypomina Szwajcarię.
Szwajcarski model federalizmu. Wnioski dla Unii Europejskiej
Keywords: federalism; Switzerland; European Union; federalizm; Szwajcaria; Unia Europejska